A multifaceted application of designed coulomb explosion occurring on oxidized topological crystalline insulator SnTe - Zhang, Guofeng; Chen, Jianbin (CrystEngComm, 2022)
Coulomb explosion, characterized by Coulomb repulsion between particles with the same charge on the surface of a material, has been used to realize exquisite nano-manipulation, however, researchers usually found only one aspect of the application of Coulomb explosion when they utilized it. Herein, we successfully design a "metal@insulator" based Coulomb explosion process by irradiating oxidized topological crystalline insulator SnTe under an electron beam. The occurrence of Coulomb explosion mainly due to the oxide-encapsulated SnTe retained the metallic surface state, which not only can be positively charged but also can realize charge accumulation through the shielding effect of the insulating oxide layer. By changing experimental conditions and carefully studying various experimental phenomena, we conclude six aspects of the application, namely, speculating the metallic surface state of the oxide-encapsulated SnTe, controllable fabricating nanoplates, observing the PVD (physical vapor deposition) process under low temperature, rapid coating film, unraveling the oriented attachment and self-recrystallization of larger nanocrystals and fabricating hollow structure. Our findings are important for utilizing Coulomb explosion as well as other EBI techniques to conduct nano-manipulation. Multifaceted application of designed coulomb explosion process occurred on the SnTe@oxide experimental model.